Analisis Penerimaan Software Akuntansi Accurate dengan Pendekatan Technology Acceptance Model (TAM) pada Badan Usaha Non Akademik Universitas Brawijaya - Dewi, Ferdilla Puspita (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2021)
BUNA is a unit at Brawijaya University that implements accounting information systems, Software Accurate in its business activities. Through Technology Acceptance Model, this study tries to examine the factors that influence the acceptance of the use of Accurate software. The collected data were analyzed using SmartPLS 3.0 software. The results of the study proved that task suitability had no significant effect on perceived benefits & ease of use, while complexity affected the benefits of use. 29.3% of perceived benefits of use are influenced by task suitability, experience, complexity & perceived ease of use. 31% perception of ease of use is influenced by task suitability, experience, complexity.70.5% of the perception of attitude towards use are influenced by the perception of the benefits of use & the perception of ease of use. And 36.8% of usage is influenced by attitudes towards use. The GoF value of 90.91% means that the model is feasible to use in predictions. For the implementation of Accurate software to be accepted by BUNA employees, it is necessary to increase the effectiveness of its use to avoid the productivity paradox.